PERAN KOMUNITAS INDONESIA PINTAR DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK DI KAMPUNG PEMULUNG PONDOK LABU JAKARTA SELATAN - Fretzelita Gatra An’nisa; Isna Rahmawati (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
AbstrakEducation is the most important aspect for the Indonesian nation. The field of education is one component that has a large enough role to create quality human beings. In Indonesia, education is divided into two, namely formal and non-formal education. Poverty is a factor that makes many students drop out of school. The high cost of education makes people choose to work for their children instead of going to school. The Smart Indonesia Community is one of the communities that provides educational counseling to disadvantaged communities in the Pondok Labu Pemulung Village, which is under the auspices of the Creative Counseling House Foundation. The research was conducted with the aim of knowing the role of the Smart Indonesia Community in carrying out teaching and learning activities and the influence of the community on increasing children's enthusiasm and motivation to learn. The method used in this research is qualitative with a descriptive approach. The data used in the study were observation and interviews. The location used in this research is the scavenger village, Pondok Labu, South Jakarta. Based on the results of the research, it shows that the Smart Indonesia Community is able to provide educational facilities, education, collaborate with foundations in providing education and facilities, as well as providing technical skills such as package schools.